Improving Students' Understanding of Mathematical Concepts Through Problem-Based Learning Held Geoboard on Plane Figures - Haerul Zaki; I Ketut Sukarma; Agusfianuddin Agusfianuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Students' understanding of mathematical concepts in the material on plane figures is still relatively low, so learning that actively involves students in constructing knowledge is needed. This study aims to improve students' understanding of mathematical concepts through the application of Problem-Based Learning(PBL) assisted by the Geoboard on the material of plane figures. This study is a Classroom Action Research (CAR) conducted in two cycles using the Kemmis and McTaggart model, which includes planning, action, observation, and reflection. The subjects were 34 seventh-grade students of SMP Islam Abu Abdillah Al Islami. Data were collected through conceptual understanding tests, observation, and documentation, then analyzed descriptively and quantitatively. The results of the study indicate that the application of Problem-Based Learning assisted by Geoboard can improve students' understanding of mathematical concepts. Classical mastery increased from 44% in cycle I to 93.93% in cycle II. Furthermore, all indicators of mathematical concept understanding improved in cycle II.